Propuesta de mejora del sistema de alistamiento de pedidos en el banco de alimentos de Bogotá - Caho Rodríguez, Julián Felipe (Universidad de La Salle. Facultad de Ingeniería. Ingeniería Industrial., 2017)
This project aims to make a proposal to improve the system of enlistment orders Bogotá Food Bank from four phases. The first is diagnostic, where it is known how the operation of the enlistment process and other processes that have direct interaction as selection and classification, scheduling and others also recognize the location and collection of the products and also the distances traveled to place orders. The second phase of the project is the identification of models location where initially the turnover rate is determined and then the different scenarios location of the products are designed and continue with the third stage design, in which taking into account the location selected models, different scenarios using different routing techniques to then identify the best method of collection products are plotted. Finally, in the fourth phase of evaluation indicators current distance found in the first phase are taken and compared with the proposed obtained in the third phase models routes to determine the design and the final distribution system enlistment food Bank orders. In developing stages raised above, is identified in the Food Bank traveled average distance for clearance of an order is 295.98 meters and the method of location and storage of references is chaotic, ie, the references are located random in the spaces available. Continuing the development of the second phase, after identifying the models compatible location with the characteristics of the food bank, the locations of the references are generated and starts with the number three phase, where routing methods combined were evaluated with the methods of location, finding the distances generated in gathering references for enlistment area, evaluating and selecting the best combination, which turned out to be the method of ABC by suppliers to the method of routing savings. Finally, each method evaluated distance and transfers between storage area enlistment was added, again comparing all possible combinations with the diagnosis initially applied, resulting in a decreased average distance to 240.4 meters, obtained from combination of location methods of product rotation method with the travel agent. Additionally it is checked whether there are significant differences between the means of the proposed combination and the current method.